1993
DOI: 10.1021/j100116a006
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular photoassociation and photoinduced charge transfer in bridged diaryl compounds. 4. Temporal studies of intramolecular triplet excimer formation in dinaphthylmethanes and dinaphthyl ethers

Abstract: Comparisons of the temporal characteristics of the transient absorption with those of the delayed fluorescence for dinaphthylmethanes and dinaphthyl ethers provide compelling kinetic evidence for the formation of intramolecular triplet excimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…In the late 1980s, there was a discussion in the literature about the existence of the naphthalene triplet excimer. Nowadays, many works support the formation of triplet excimers of dinaphthyl compounds under various conditions. ,, In the experimental work by Terazima, Cai, and Lim, covalently linked naphthalene dimers were studied using time-resolved electronparamagnetic resonance (TREPR), phosphorescence, and transient absorption measurements . From the interpretation of these spectra, they suggested that these compounds form triplet excimers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the late 1980s, there was a discussion in the literature about the existence of the naphthalene triplet excimer. Nowadays, many works support the formation of triplet excimers of dinaphthyl compounds under various conditions. ,, In the experimental work by Terazima, Cai, and Lim, covalently linked naphthalene dimers were studied using time-resolved electronparamagnetic resonance (TREPR), phosphorescence, and transient absorption measurements . From the interpretation of these spectra, they suggested that these compounds form triplet excimers.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the naphthalene triplet dimer shows, depending on its molecular conformation, the two extreme cases of strong and weak coupling with and without π−π-interactions between the monomers (vide infra). Intermediate cases also can be realized experimentally by covalently linked naphthalene molecules with a defined conformation. , ,, Hence, the naphthalene dimer in the first triplet excited state is a perfect model system for the investigation and understanding of triplet−triplet interactions between molecules with π-systems.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility, prompted by the long lifetime and small zero-field splittings, involves an association or charge transfer between adjacent phenyl moieties of the phosphine or arsine ligands. This could occur either intermolecularly or intramolecularly, leading to red-shifted 1,3 *^ ß states (excimer or CT) 43 The emission in such cases should be characterized by highfrequency, internal modes of a phenyl group and low-frequency, external motions of the interacting phenyl groups. Such an excited state might also be favored by the perturbed orientations of the interacting phenyl groups at some deep trap site.…”
Section: Discussionmentioning
confidence: 99%
“…These results, shown in Figure 4, demonstrate that the bimolecular annihilation of the species responsible for the absorption (i.e" triplet excimer) is also responsible for the emission identified as the delayed excimer fluorescence. 2 The emission maximum of the delayed excimer fluorescence, which is the major component, lies slightly to the red of the intensity maximum of the monomer fluorescence.…”
Section: Resultsmentioning
confidence: 98%